Shifting gears: Id3 enables recruitment of E proteins to new targets during T cell development and differentiation - Anderson, Michele K. (Frontiers in Immunology, 2022)
Shifting levels of E proteins and Id factors are pivotal in T cell development and differentiation, both in the thymus and in the periphery. Although they use the same mechanism to suppress E protein activity, Id2 and Id3 play very different roles in T cell development and CD4 T cell differentiation. Id2 imposes an irreversible choice between innate and adaptive lineages. By contrast, Id3 acts in a transient fashion downstream of T cell receptor (TCR) signaling, resulting in the dislodging of E proteins from their target sites while chromatin remodeling occurs. After the cessation of Id3 expression, E proteins can induce newly accessible target genes. To describe this mode of action, we have developed the “Clutch” of differentiation. In this model, Id3 upregulation acts as a clutch that stops E protein activity (“clutch in”) long enough to allow shifting of the genomic landscape into a different “gear”, resulting in accessibility to different E protein target genes (“clutch out”). While TCR signal strength and cytokine signaling play a role in both peripheral and thymic lineage decisions, the remodeling of chromatin and E protein target genes appears to be more heavily influenced by the cytokine milieu, whereas the outcome of Id3 activity during T cell development in the thymus appears to depend more on the TCR signal strength. New emerging technologies should enable a better understanding of the molecular events that happen during these transitions, and how they fit into the gene regulatory networks that drive T cell development and differentiation.